2019
DOI: 10.1080/21645698.2019.1612689
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost of regulating genome edited crops: expert judgment and overconfidence

Abstract: Experts are often called on to inform decision makers with subjective estimates of uncertain events. Their judgment serves as the basis for policy-related decision-making. This paper analyzes survey results used to collect experts' opinions of the likely cost to bring genome edited crops to market. We also examine the effect of expertise (scientific experts versus social scientists in plant biotechnology) and possible knowledge mis-calibration, both in terms of overconfidence (i.e., when subjective knowledge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…However, there are some reasons to believe that the general finding of overconfidence (among both ‘experts’ and laypeople) is likely to generalize to a number of contexts in which COVID-19 forecasts (and presumably epidemiological forecasts more generally) are made. First, the finding of overconfidence among individuals with relevant subject-matter expertise is consistent with, in the words of Philip Tetlock, “a multi-decade line of psychological research on expert judgment that has shown that experts in a wide range of fields are prone to think they know more than they do (the overconfidence effect)” [ 26 ]; other researchers have described overconfidence as “the most ubiquitous bias in studies of calibrated judgments about risks and uncertainties” [ 27 ]. Research summarizing relevant studies across a wide variety of fields finds systematic overconfidence in judgments made by both lay predictors and those with relevant expertise [ 28 – 30 ].…”
Section: Discussionsupporting
confidence: 62%
“…However, there are some reasons to believe that the general finding of overconfidence (among both ‘experts’ and laypeople) is likely to generalize to a number of contexts in which COVID-19 forecasts (and presumably epidemiological forecasts more generally) are made. First, the finding of overconfidence among individuals with relevant subject-matter expertise is consistent with, in the words of Philip Tetlock, “a multi-decade line of psychological research on expert judgment that has shown that experts in a wide range of fields are prone to think they know more than they do (the overconfidence effect)” [ 26 ]; other researchers have described overconfidence as “the most ubiquitous bias in studies of calibrated judgments about risks and uncertainties” [ 27 ]. Research summarizing relevant studies across a wide variety of fields finds systematic overconfidence in judgments made by both lay predictors and those with relevant expertise [ 28 – 30 ].…”
Section: Discussionsupporting
confidence: 62%
“…This is also true of CRISPR/Cas9-modified food crops, when in 2016, a common button mushroom ( Agaricus bisporus ), modified to resist browning and thus reduce spoilage, was granted non-regulated status ( Waltz, 2016 ). Since then, several gene edited products have already entered the market: Calyno TM , a high oleic soybean oil, SU (sulfonylurea) Canola TM , a herbicide tolerant canola and a waxy corn ( Lassoued et al, 2019 ; USDA APHIS, 2020b ). For an in-depth analysis of the regulations applicable to genome editing in the United States, see Wolt and Wolf (2018) ( Table 2 ).…”
Section: An Overview Of the Global Legislative Landscapementioning
confidence: 99%
“…The role that domestic and international regulations have played in inhibiting agricultural innovation and the development of consumer-focused traits has been greatly under-appreciated. If the costs of regulatory processes are high and the timelines and outcomes are unpredictable, the development process is both risky and expensive (Ludlow et al 2014;Smyth and Lassoued 2019;Zimny et al 2019;Zimny and Eriksson 2020.). These costs and uncertainties have limited the types of GE traits that have come to market, as well as the types of GE crops.…”
Section: Regulatory Impacts On International Trade and Innovationmentioning
confidence: 99%